2019
DOI: 10.1152/ajprenal.00381.2018
|View full text |Cite
|
Sign up to set email alerts
|

Tubule-vascular feedback in renal autoregulation

Abstract: Afferent arteriole (Af-Art) diameter regulates pressure and flow into the glomerulus, which are the main determinants of the glomerular filtration rate. Thus, Af-Art resistance is crucial for Na+ filtration. Af-Arts play a role as integrative centers, where systemic and local systems interact to determine the final degree of resistance. The tubule of a single nephron contacts an Af-Art of the same nephron at two locations: in the transition of the thick ascending limb to the distal tubule (macula densa) and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
13
0
5
Order By: Relevance
“…Tubular chloride reabsorption leads to the renal vasoconstrictive effect and responsible for acute kidney injuries 3 . Also, high tubular chloride reabsorption activates the tubule‐glomerular feedback and reduces the glomerular filtration rate 21 . Chloride‐liberal intravenous fluid (angiotensin II antagonist) induces thromboxane release that is associated with vasoconstriction 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubular chloride reabsorption leads to the renal vasoconstrictive effect and responsible for acute kidney injuries 3 . Also, high tubular chloride reabsorption activates the tubule‐glomerular feedback and reduces the glomerular filtration rate 21 . Chloride‐liberal intravenous fluid (angiotensin II antagonist) induces thromboxane release that is associated with vasoconstriction 3 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Also, high tubular chloride reabsorption activates the tubule-glomerular feedback and reduces the glomerular filtration rate. 21 Chloride-liberal intravenous fluid (angiotensin II antagonist) induces thromboxane release that is associated with * Significantly lower than a chloride-liberal cohort vasoconstriction. 3 The current study reported that several mechanisms through chloride-liberal intravenous fluid may cause acute kidney injuries.…”
Section: Discussionmentioning
confidence: 99%
“…HIF1a induces CD73 (ecto-5-prime-nucleotidase) (Synnestvedt et al, 2002) and increases adenosine signaling. In the kidney, adenosine is a vasoconstrictor involved in tubuloglomerular feedback responses (Schnermann, 2015;Romero and Carretero, 2019). Upregulation of CD73 has been reported to protect the kidney from ischemia-reperfusion injury and diabetic nephropathy (Tak et al, 2014;Sung et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension usually lasts for >10 years before the gradual emergence of nocturia, mild proteinuria and other associated clinical symptoms ( 14 ). This disease is usually preceded by distal tubular dysfunction, followed by glomerular dysfunction ( 15 , 16 ). The patient's renal pathology starts with renal arteriopathy, followed by ischemic renal parenchymal damage ( 11 ).…”
Section: Pathogenesis Of Hypertensive Nephropathymentioning
confidence: 99%